NONLINEAR, HETEROGENEOUS AND MEDIATING EFFECTS OF INSTITUTIONAL OWNERSHIP ON ENTERPRISE INNOVATION: EVIDENCE FROM CHINESE LISTED ENTERPRISES - Cui, Zhaocai; Xiao, Yue; Li, Cheng (International Journal of Innovation Management, 2022)
Based on the microdata of Chinese listed enterprises from 2012 to 2017, we empirically examine the nonlinear relationship between institutional ownership and enterprise innovation. We find that institutional ownership has an inverted-U nonlinear relationship with enterprise patenting when enterprise characteristics and fixed effects such as time, region, industry type and ownership type of enterprises (SOE or NSOE) are controlled and the endogeneity is considered. This nonlinear relationship significantly varies among active, passive, pressure-resistant and pressure-sensitive groupings of institutional investors. Employing the mediation model proposed by Hayes and Preacher (2010) [Quantifying and testing indirect effects in simple mediation models when the constituent paths are nonlinear. Multivariate Behavioral Research, 45(4), 627-660], we further investigate the mediating effects of financing constraints and R&D manipulation. The results show that institutional ownership linearly drives enterprise innovation by alleviating financing constraints but nonlinearly affects the enterprise innovation by manipulating R&D activities.
CRIS-Team WoS Importer:2022-10-28

Pathways to scaling up in emerging economies: A configurational analysis of organizational capabilities in social enterprises - Xiao, Yue (Journal of Business Research, 2025)
Organizational capability is a key factor influencing the effectiveness of scaling social impact within social enterprises, yet the combined effects of specific capabilities have been largely overlooked by existing studies. Utilizing the SCALERS model, this research examines how different configurations of organizational capabilities contribute to high-performance scaling up in entrepreneurially vibrant regions of emerging economies. Based on a configurational analysis of 46 purposively selected Chinese social enterprises, this study identifies five effective pathways catering to social enterprises with varying replicable programs, connection capacities, and self-development capabilities. These pathways remain robust when government attention and public attention are considered situational contingencies. Additionally, this study reveals a high level of consistency across pathways in achieving overall social impact and its specific quantitative and qualitative dimensions. This study bridges the gap in examining the synergistic potential of organizational capabilities and provides a more fine-grained investigation of scaling up.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Emerging economies; Organizational capability; Qualitative comparative analysis; SCALERS model; Scaling up; Social enterprise

Where Two Are Fighting, the Third One Does What? Digitalisation and Its Effects on Social Entrepreneurship's Social Economic Hybridity. - Xiao, Yue; Beckmann, Markus (Journal of Social Entrepreneurship, 2024)